Lung disease and ulcerative colitis − mesalazine-induced bronchiolitis obliterans with organizing pneumonia or pulmonary manifestation of inflammatory bowel disease? - Moeser, A.; Pletz, M. W.; Hagel, S.; Kroegel, C.; Stallmach, A. (Zeitschrift für Gastroenterologie, 2015)
Ulcerative colitis can be associated with numerous extraintestinal organ manifestations. Pulmonary disease in inflammatory bowel disease (IBD) is supposed to be a rare entity and has to be distinguished from infectious complications and side-effects of medications used in the treatment of IBD. We present the case of a 20-year-old male patient with ulcerative colitis and a 4-week history of respiratory symptoms, malaise, fever and respiratory insufficiency under a medication with mesalazine. Computed tomography showed bilateral subpleural consolidations, bronchoscopy revealed signs of acute bronchitis. The diagnostic work-up ruled out an infectious cause. Under the tentative diagnosis of a mesalazine-induced bronchiolitis obliterans with organizing pneumonia (BOOP) the medication with mesalazine was withdrawn and the patient received a corticosteroid trial. The symptoms quickly improved and prednisone was tapered and stopped after 6 months. Unexpectedly, lung function after complete resolution of respiratory symptoms revealed a residual obstructive ventilatory defect that might be due to an asymptomatic pulmonary manifestation of ulcerative colitis. A review of the literature shows that pulmonary manifestations in IBD as well as pulmonary toxicity of mesalazine might not be as rare as expected and should be included as differential diagnoses in the work-up of respiratory symptoms in patients with IBD. A pragmatic therapeutic approach is reasonable in critically ill patients as it is not always easy to distinguish both entities.
Keywords: chronisch entzündliche Darmerkrankung; Colitis ulcerosa; extraintestinale Manifestation